Perbedaan Minat Belajar dan Motivasi Belajar Ditinjau dari Penggunaan Metode Menghafal Alquran di Pondok Tahfidz Maskanul Huffaz di Bintaro - Qodri, Muhammad; Lubis, Rahmi; Hardjo, Suryani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to determine the differences in learning interest and learning motivation in terms of the use of the At-Taisir Qur'an memorization method and Dermawan's Qur'an memorization method. The research method uses a quantitative approach, with a purposive sampling technique. The population in this study amounted to 62 and a sample of 40 students were divided into 2 groups, namely 20 data from each group. The analytical method used to analyze the data obtained in this study uses the Mann Whitney U analysis method. In the At-Taisir method, the learning interest scale is in the low category with an empirical mean of 23.40 and a hypothetical mean of 45 with sd 9. The learning motivation scale is in the very category. low with an empirical mean of 57.25 and a hypothetical mean of 97.5 with an sd of 19.5. Whereas in the Dermawan method, the interest scale category is very high, the empirical mean is 68.30 and the hypothetical mean is 45 with sd 9. The motivation scale in the category is very high, the empirical mean is 141.90 and the hypothetical mean is 97.5 with sd 19.5. The results of this study indicate that the significance value of Mann Whitney U is 0.000, which means that the difference between learning motivation in students using the At-Taisir method and the Dermawan method is accepted. In the learning interest group, a result of 0.000 was obtained, which means that there was no difference between students' learning interest when studying using the At-Taisir method and the Dermawan method, meaning that this research was accepted because it was in accordance with the initial hypothesis.